Dentistry and Drug Adverse Events: Between Responsibilities and Regulations - Tommaso D’Anna; Antonina Argo; Stefania Zerbo; Diego D’Urso; Maria Sofia Rini (Toxics, 2022)
The purpose of this paper is to renew interest and attention to the medical history, prescription, and/or use of drugs during dental practice. The work analyzes the issue of the use of drugs in dentistry from both a clinical and a medical–legal point of view. The laws governing the matter were also taken into consideration, relating them to the roles of prescriber and user that the dentist can acquire. Analysis of various aspects of this matter demonstrates that it is necessary for dentists to know the drugs and medical substances, their characteristics and properties, related effects, and interactions in order to use them appropriately and adequately. Knowledge of interferences, reactions, and adverse events or complications helps to reduce errors and protect patients’ health. Furthermore, knowledge of the national and international reference standards relating to the use of drugs leads to a reduction in medico–legal questions. In conclusion, knowledge and adequate and appropriate use of drugs reduces the possibility of accidents, adverse events, medico–legal consequences, and disputes with patients. Documented and traceable choices allow the analysis and valuation of professional conduct. Authors perceived the topic of informed consent of patients as relevant to the adequate procedure of prescribing drugs related to dentistry practice; therefore, representative conditions of patients at risk should be illustrated in practice. Legal duties related to physician drug prescription and use must be considered and carefully checked.